THE INFLUENCE OF WORK ETHOS, WORK ENVIRONMENT AND WORK MOTIVATION ON THE PERFORMANCE - Susi Listiani; Prihatin Lumbanraja; Pardamean Daulay (Faculty of Economic and Business, University of Pasundan, 2022)
This study aims to examine how the influence of work ethic, work environment and work motivation on the performance of public high school education personnel in the city of Padangsidimpuan partially and simultaneously. This research was conducted using a quantitative approach with a survey method. From the results of the partial hypothesis test, it is stated that the work ethic variable has a positive and significant effect on the performance of educational staff, the work environment variable has a positive but not significant effect on educational staff, and work motivation has a positive and significant effect on the performance of educational staff. From the results of the simultaneous test, it is known that the variables of work ethic, work environment and work motivation have a positive and significant influence on the performance of educational staff.